UV cured thiol-ene flame retardant hybrid coatings - OKTAY, BURCU; KAHRAMAN, MEMET VEZİR; KAYAMAN APOHAN, NİLHAN (ELSEVIER SCIENCE SA, 2013)
In this study, bis-(triethoxysilylpropyl) phenyl phosphamide (BESPPA) was synthesized by the reaction between dichlorophenyl phosphine oxide and 3-aminopropyltriethoxysilane. The chemical structure of the BESPPA was characterized with Fourier transform infrared and NMR techniques. Flame retardant, BESPPA and sol gel precursor containing hybrid materials were prepared by thiol-ene polymerization with the aim to improve their final thermal and flame retardant properties. The thermal stabilities of the phosphorous/sol-gel containing UV-cured hybrid materials were investigated by thermogravimetric analysis. The results showed that the addition of sol-gel precursor and BESPPA into the organic network also improves the thermal-oxidative stability of the hybrid materials. The flame-retardant properties of the UV-cured hybrid materials were also studied. Furthermore, the phosphorus silicon synergistic effect on LOI enhancement and increasing flame retardancy of the UV-cured hybrid materials were demonstrated. An LOI enhancement from 20.7 to 26.5 is observed for organic resins containing both phosphorus and silicon. The surface morphology was also characterized by scanning electron microscopy (SEM). SEM studies indicated that inorganic particles were dispersed homogenously throughout the organic matrix. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Thiol-ene polymerization; Flame retardant; Phosphorus; UV curing; Sol-gel; PHOSPHORUS-CONTAINING EPOXY; PHOTOCURED COATINGS; SILICON; SYSTEMS; RESINS